1991
DOI: 10.1017/s002185960006531x
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phosphorus and potassium from the soil in wheat and barley straw

Abstract: S U M M A R YThe median concentration of phosphorus and potassium in a total of 867 samples of wheat and barley straw at harvest in England in 1986-88 was 0-07% P and 100% K in the dry matter. Variation was significant between years and between crop species. The concentration of potassium in wheat and barley straw increased with increasing rate of applied nitrogen at 60% of the sites where this was tested. The results have been incorporated into practical recommendation systems for farmers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…There can also be variation in nutrient contents of straws between sites and across years (Withers 1991).…”
Section: Nutrient Substitution Penaltymentioning
confidence: 99%
See 1 more Smart Citation
“…There can also be variation in nutrient contents of straws between sites and across years (Withers 1991).…”
Section: Nutrient Substitution Penaltymentioning
confidence: 99%
“…It is suggested that N requirements increase if straw is incorporated, due to immobilisation of N during straw decomposition (Limon-Ortega et al 2008), therefore it is inappropriate to include N substitution (Kindred et al 2008). Databases listing the nutrient content of straw suggest that it is responsible for K recycling, rather than P or N (Agro Business Consultants Ltd 2011; PDA n.d.; Withers 1991).…”
Section: Nutrient Substitutionmentioning
confidence: 99%
“…Assuming that this increase in uptake was mainly due to the K released from the previous barley crop (which contained c 90 kg K ha~1), the efficiency of K transfer was c 45È50%. Using average straw yield data (Nix 1995) and typical K contents (ARC 1976 ;Withers 1991) it is suggested that, in the absence of soil analysis, K fertiliser input to beet should be reduced by 20 kg K ha~1 when there has been a history of straw incorporation. This estimate assumes that the K supply in the unincorporated soil was adequate, and that the excess K uptake observed in the straw incorporated plots was due to luxury consumption.…”
Section: Modiðcations To K Fertiliser Inputs When Straw Is Incorporatedmentioning
confidence: 99%